A link between internet addiction and attention deficit hyperactivity disorder symptoms in Pakistani undergraduates - Tufail, Muhammad Waseem; Khan, Rahmattullah; Muhammad Saleem, (Penerbit Universiti Kebangsaan Malaysia, 2015)
The current research aims to establish a link between internet addiction and Attention Deficit Hyperactivity Disorder (ADHD) Symptoms among Pakistani Undergraduates. The sample comprised of (N =1020) undergraduates from Bahauddin Zakariya University Multan (BZU) and The Islamia University of Bahawalpur (IUB), Pakistan, including 255 male and 255 female from each university. A-Priori sample size was estimated with 974 participants, to consider sample size sufficiency, twenty three respondents were taken additionally from each university. There were two questionnaires employed; Chen Internet Addiction Scale by © Ko et al. (2005), and ADHD Adult Self Reporting Scale (ASRS) by © Kessler et al. (2005). Cross-sectional survey research design was used. Data were collected through purposive sampling and analyzed by use of SPSS (21.0). Regression, t-Test, mean, and standard deviation were employed. The result depicts; overall 28% students fulfill the criteria of internet addiction, and comparatively BZU students have higher prevalence of internet addiction with ADHD symptoms as compared to IUB. Likewise, male students are found more vulnerable towards ADHD symptoms and internet addiction as compared to female students. Study proved the significant relation of internet addiction with ADHD symptoms (0.082*). Finally, implications, significance of the study, and limitation are enclosed.